Post-mortem correlates of in vivo PiB-PET amyloid imaging in a typical case of Alzheimer's disease - Ikonomovic, Milos D.; Klunk, William E.; Abrahamson, Eric E.; Mathis, Chester A.; Price, Julie C.; Tsopelas, Nicholas D.; Lopresti, Brian J.; Ziolko, Scott; Bi, Wenzhu; Paljug, William R.; Debnath, Manik L.; Hope, Caroline E.; et al. (Brain (London, England : 1878), 2008)
The positron emission tomography (PET) radiotracer Pittsburgh Compound-B (PiB) binds with high affinity to β-pleated sheet aggregates of the amyloid-β (Aβ) peptide in vitro. The in vivo retention of PiB in brains of people with Alzheimer's disease shows a regional distribution that is very similar to distribution of Aβ deposits observed post-mortem. However, the basis for regional variations in PiB binding in vivo, and the extent to which it binds to different types of Aβ-containing plaques and tau-containing neurofibrillary tangles (NFT), has not been thoroughly investigated. The present study examined 28 clinically diagnosed and autopsy-confirmed Alzheimer's disease subjects, including one Alzheimer's disease subject who had undergone PiB-PET imaging 10 months prior to death, to evaluate region- and substrate-specific binding of the highly fluorescent PiB derivative 6-CN-PiB. These data were then correlated with region-matched Aβ plaque load and peptide levels, [3H]PiB binding in vitro, and in vivo PET retention levels. We found that in Alzheimer's disease brain tissue sections, the preponderance of 6-CN-PiB binding is in plaques immunoreactive to either Aβ42 or Aβ40, and to vascular Aβ deposits. 6-CN-PiB labelling was most robust in compact/cored plaques in the prefrontal and temporal cortices. While diffuse plaques, including those in caudate nucleus and presubiculum, were less prominently labelled, amorphous Aβ plaques in the cerebellum were not detectable with 6-CN-PiB. Only a small subset of NFT were 6-CN-PiB positive; these resembled extracellular ‘ghost’ NFT. In Alzheimer's disease brain tissue homogenates, there was a direct correlation between [3H]PiB binding and insoluble Aβ peptide levels. In the Alzheimer's disease subject who underwent PiB-PET prior to death, in vivo PiB retention levels correlated directly with region-matched post-mortem measures of [3H]PiB binding, insoluble Aβ peptide levels, 6-CN-PiB- and Aβ plaque load, but not with measures of NFT. These results demonstrate, in a typical Alzheimer's disease brain, that PiB binding is highly selective for insoluble (fibrillar) Aβ deposits, and not for neurofibrillary pathology. The strong direct correlation of in vivo PiB retention with region-matched quantitative analyses of Aβ plaques in the same subject supports the validity of PiB-PET imaging as a method for in vivo evaluation of Aβ plaque burden.